Why is Russian Domestic War Propaganda so Effective? - Dergacheva, Alexandra Cheveleva (Global Journal of Cultural Studies, 2022)
This article provides a review of possible causes of the effectiveness of the Russian domestic propaganda campaigns launched in connection with the war in Ukraine and aimed at the domestic consumer, as well as their discussion in academic research and analytical publications. Currently, this phenomenon is much discussed in the oppositional Russian-speaking, Ukrainian, and world media. Nevertheless, the number of short journalistic pieces devoted to specific aspects of this effectiveness significantly prevails over detailed analytical articles or holistic academic studies. The present research aims to partially fill this gap. The article defines the main groups of reasons for the effectiveness of Russian domestic propaganda, identified both in modern studies and in earlier works, and also traces the relationship between these groups. It discusses the organizational and technical prerequisites (the possibility of total control of the media, including access to information via the Internet), cultural issues (the unique situation in Russia, which has developed as a result of its transgenerational traumas), and "political technology" (political manipulation and persuasion) methods. In conclusion, the author makes some suggestions (and assumptions) about further possibilities for studying the phenomenon of Russian domestic propaganda and discusses its social significance.